Being and nothingness - Sartre, Jean-Paul, 1905-1980. (New York : Gramercy Books ; Avenel, N.J. : distributed by Random House, 1994)
The classic essential text of existentialist philosophy.
Originally published: New York : Philosophical Library, 1956.
Includes index.
Keywords: Existentialism; Existential psychology